If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-1y + -4w + 3) = 0 Reorder the terms: -1(3 + -4w + -1y) = 0 (3 * -1 + -4w * -1 + -1y * -1) = 0 (-3 + 4w + 1y) = 0 Solving -3 + 4w + 1y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 4w + 3 + 1y = 0 + 3 Reorder the terms: -3 + 3 + 4w + 1y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 4w + 1y = 0 + 3 4w + 1y = 0 + 3 Combine like terms: 0 + 3 = 3 4w + 1y = 3 Add '-1y' to each side of the equation. 4w + 1y + -1y = 3 + -1y Combine like terms: 1y + -1y = 0 4w + 0 = 3 + -1y 4w = 3 + -1y Divide each side by '4'. w = 0.75 + -0.25y Simplifying w = 0.75 + -0.25y
| (3y)=x-2x | | -5(-1)(-3)(-3)= | | 6(11-2)=54 | | P+9=56 | | 7+3*x=31 | | P+a=56 | | (3y)=x-2xsquared | | P+a=55 | | 5n-10=37 | | X=63-x/0.4 | | -3+(N+1)=12 | | wn2/3w=5/8 | | Log(9x+7)=1 | | (h+9)=2x-6 | | N+[4-2(3-5)]=6 | | bj=104 | | -17+a=-(-10) | | 1=3.5t | | 0.75(12x+8)=2x-15 | | .19*.23=x | | .19*.23= | | 2x-5=27-6x | | 3(u+3)-7u=37 | | (4s)^5/(4s)^12 | | 2xn=8xn+30 | | 164=121-y | | 50*25h=125 | | -0.3333333333=75-15 | | a/5-5/6=-1/2 | | 4x^3-4x^2-9x+12=0 | | -20c=34 | | 10+x=-52 |